A Combination of Data Augmentation Techniques for Mango Leaf Diseases Classification (Global Journal of Computer Science and Technology, 2023)
Mango is one of the most traded fruits in the world Therefore mango production suffers from several pests and diseases which reduce the production and quality of mangoes and their price in the local and international markets Several solutions for automatic diagnosis of these pests and diseases have been proposed by researchers in the last decade These solutions are based on Machine Learning ML and Deep Learning DL algorithms In recent years Convolutional Neural Networks CNNs have achieved impressive results in image classification and are considered as the leading methods for image classification
Keywords: data augmentation; mango; disease; classification; deep learning; resnet50